Promotional Genre in Research Article Abstracts (RAAs) in the Applied Linguistics Discipline - Warsidi (Universitas Islam Negeri Palopo, 2026)
While understanding promotional genre in research article abstracts (RAAs) has important role to promote research and attract targeted audiences, studies in these potential topics are still limited in the literature. This study aims to analyze promotional genre, communicative functions to promote research, in English RAAs by addressing two important goals: identifying to what extent is research promoted in the abstract section in the applied linguistics discipline, and discover communicative strategies employed to promote research in the RAAs. In responding these goals, it used genre approach to analyze 30 RAAs in the applied linguistics discipline published in reputable journals in Q1 Scopus indexed journals with Scimago Journal Rank (SJR) higher than 1.0 using a qualitative genre analysis. The results revealed that 29 of 30 RAAs promote their research in this section, and they used three communicative strategies to promote their research. These three communicative strategies include: promoting the importance of the current research topics, promoting the importance of the findings, and promoting the implication and contribution of the study. This study may contribute to expand genre studies in the literature and contribute to academic writing in research practices and writing pedagogies.